Update of the best practice dietetic management of overweight and obese children and adolescents: a systematic review protocol. (July 2018) - Shrewsbury, Vanessa A.; Burrows, Tracy; Ho, Mandy; Jensen, Megan; Garnett, Sarah P.; Stewart, Laura; Gow, Megan L.; Ells, Louisa J.; Chai, Li Kheng; Ashton, Lee; Walker, Jacqueline L.; Littlewood, Robyn; et al.
Abstract : Review question/objective: To update an existing systematic review series1, 2 of randomized controlled trials (RCT) that include a dietary intervention for the management of overweight or obesity in children or adolescents. Specifically, the review questions are: In randomized controlled trials of interventions which include a dietary intervention for the management of overweight or obesity in children or adolescents: What impact do these interventions have on participants' adiposity and dietary outcomes? What are the characteristics or intervention components that predict adiposity reduction or improvements in dietary outcomes?